1987
DOI: 10.1093/jac/19.5.647
|View full text |Cite
|
Sign up to set email alerts
|

Co-trimoxazole versus nafcillin in the therapy of experimental meningitis due to Staphylococcus aureus

Abstract: Co-trimoxazole was compared with nafcillin against Staphylococcus aureus in vitro and in the therapy of experimental Staph. aureus meningitis in rabbits. Co-trimoxazole (trimethoprim:sulphamethoxazole in a 1:20 ratio) was synergistic against 22/24 strains of Staph. aureus in vitro. The MBC90 of co-trimoxazole and nafcillin were 0.156-3.12 mg/l and 0.25 mg/l, respectively, concentrations below those achievable in purulent cerebrospinal fluid. The rate of bacterial killing (Staph. aureus) by co-trimoxazole and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Previous studies showed that the MBC of TMP-SMX for staphylococci did increase when the inoculum was raised from 10 5 to 10 7 CFU per ml (24). In our studies, the kinetics of killing of staphylococci assessed by the time-kill method with high inocula showed a slow and modest decrease in the number of microorganisms, which predicted a suboptimal in vivo effect.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Previous studies showed that the MBC of TMP-SMX for staphylococci did increase when the inoculum was raised from 10 5 to 10 7 CFU per ml (24). In our studies, the kinetics of killing of staphylococci assessed by the time-kill method with high inocula showed a slow and modest decrease in the number of microorganisms, which predicted a suboptimal in vivo effect.…”
Section: Discussionsupporting
confidence: 55%
“…To the best of our knowledge, only one experimental study has addressed the comparative efficacy of TMP-SMX versus other antimicrobial agents against S. aureus in vivo (24). Using the experimental model of meningitis, Scheld et al showed that TMP-SMX killed S. aureus at a slower rate and more incompletely than nafcillin did (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TMP-SMZ was less active than vancomycin in a rabbit model of MRSA endocarditis and less rapidly bactericidal than nafcillin in a rabbit model of MSSA meningitis [78,79]. A randomized trial of treatment of S. aureus infections, 47% of which were due to MRSA, concluded that treatment with TMP-SMZ was inferior to treatment with vancomycin [80].…”
Section: Available Antibiotics For the Treatment Of Mrsa Infectionmentioning
confidence: 99%
“…These data suggest that for MRSA infection, T/S may be equivalent in efficacy to vancomycin and might even be associated with faster clinical improvement. However, other studies have shown a less rapid bactericidal effect for T/S than for beta-lactams or vancomycin, 76 so T/S is not recommended for treatment of serious infections (e.g., endocarditis) where more rapid killing is thought to be necessary, though it may be an option for nonbacteremic skin and soft tissue infections.…”
Section: Clinical Experiencementioning
confidence: 99%